Կովսական-Քաշունիքի Սյունիները - Ժ. Ա. Միրումյան (ՀՀ ԳԱԱ հրատ.)
Ковсакан и Кашуник являлись южными регионами исторического Сюника. На основе сравнительного анализа рукописных источников можно утверждать, что князья княжеского дома Сюни–Ковсакан Кашуника поочередно княжили в южных регионах Сюника с конца восьмого века до падения царства Сюника в 1170 г. Both Kovsakan and Qashuni were southern provinces of the Syunik Region. The present article briefly refers to the time period of the formation of the Prince Dynasty of the Syunies of Kovsakan-Qashuni and their relations to the crowned princes of Syunik. The name list and family tree of the Syunies of Kovsakan-Qashuni is also considered in the article, resulting from the comparative analysis of the corresponding historical data.
Keywords: Auxiliary Sciences of History; Geography; Anthropology; Recreation; Medieval History; Geography; Genealogy; History; D History